Optimal Outcome in Individuals with a History of Autism - Fein, Deborah (2013)
BACKGROUND: Although Autism Spectrum Disorders (ASDs) are generally considered lifelong disabilities, literature suggests that a minority of individuals with an ASD will lose the diagnosis. However, the existence of this phenomenon, as well as its frequency and interpretation, is still controversial: were they misdiagnosed initially, is this a rare event, did they lose the full diagnosis but still suffer significant social and communication impairments or did they lose all symptoms of ASD and function socially within the normal range? METHODS: The present study documents a group of these optimal outcome individuals (OO group, n=34) by comparing their functioning on standardized measures to age, sex, and nonverbal IQ matched individuals with high-functioning autism (HFA group, n=44) or typical development (TD group, n=34). For this study, ‘optimal outcome’ requires losing all symptoms of ASD in addition to the diagnosis, and functioning within the non-autistic range of social interaction and communication. Domains explored include language, face recognition, socialization, communication, and autism symptoms. RESULTS: OO and TD groups’ mean scores did not differ on socialization, communication, face recognition, or most language subscales, although three OO individuals showed below-average scores on face recognition. Early in their development, the OO group displayed milder symptoms than the HFA group in the social domain, but had equally severe difficulties with communication and repetitive behaviors. CONCLUSIONS: Although possible deficits in more subtle aspects of social interaction or cognition are not ruled out, the results substantiate the possibility of optimal outcome from autism spectrum disorders and demonstrate an overall level of functioning within normal limits for this group.